Evolution of E. coli Phytase Toward Improved Hydrolysis of Inositol Tetraphosphate - Herrmann, Kevin R.; Brethauer, Christin; Siedhoff, Niklas E.; Hofmann, Isabell; Eyll, Johanna; Davari, Mehdi D.; Schwaneberg, Ulrich; Ruff, Anna Joëlle (Frontiers in Chemical Engineering, 2022)
Protein engineering campaigns are driven by the demand for superior enzyme performance under non-natural process conditions, such as elevated temperature or non-neutral pH, to achieve utmost efficiency and conserve limited resources. Phytases are industrial relevant feed enzymes that contribute to the overall Phosphorus (P) management by catalyzing the stepwise phosphate hydrolysis from phytate which is the main Phosphorus storage in plants. Phosphorus is referred to as a critical disappearing nutrient, emphasizing the urgent need to implement strategies for a sustainable circular use and recovery of P from renewable resources. Engineered phytases already contribute today to an efficient Phosphorus mobilization in the feeding industry and might pave the way to a circular P-bioeconomy. To date, a bottleneck in its application is the drastically reduced hydrolysis on lower phosphorylated reaction intermediates (lower inositol phosphates, ≤ InsP4) and their subsequent accumulation. Here, we report the first KnowVolution campaign of the E. coli phytase towards improved hydrolysis on InsP4 and InsP3. As a prerequisite prior to evolution, a suitable screening setup was established and the three isomers Ins(2,4,5)P3, Ins(2,3,4,5)P4 and Ins(1,2,5,6)P4 were generated through enzymatic hydrolysis of InsP6 and subsequent purification by HPLC. Screening of epPCR libraries identified clones with improved hydrolysis on Ins(1,2,5,6)P4 carrying substitutions involved in substrate binding and orientation. Saturation of seven positions and screening of in total ten thousand clones generated a dataset of 46 variants on their activity on all three isomers. This dataset was used for training, testing and inferring models for machine learning guided recombination. The PyPEF method used allowed the prediction of recombination from the identified substitutions, which were analyzed by reverse engineering to gain molecular understanding. Six variants with improved InsP4 hydrolysis of > 2.5 were identified, of which variant T23L/K24S had a 3.7-fold improved relative activity on Ins(2,3,4,5)P4 and concomitantly shows a 2.7-fold improved hydrolysis of Ins(2,4,5)P3. Reported substitutions are the first published Ec phy variants with improved hydrolysis on InsP4 and InsP3.